Adoption of e-government in Colombia: the importance of government policy in citizens' use of e-government. (8th March 2021) - Sánchez-Torres, J.A.; Arroyo-Cañada, F.J.; Varon-Sandoval, Alexander; Sánchez-Alzate, J.A.
This article aims to describe the key e-government adoption factors for the citizens of Colombia to determine whether government policies aimed at the use of the internet as a tool for the use of e-government are effective. A comprehensive model based on the technology acceptance model theory is proposed, while also introducing the variable of government support. 445 surveys were collected across the country using the internet. The data analysis was conducted through structural equation modelling using PLS 3.0 software. The results show that performance expectations, as well as governmental support and trust, have a great influence on the adoption of e-government. The results confirm that citizens value the policies on virtual connectivity with their public institutions that are being implemented, though the construct of effort expectancy is not validated. This research is one of the first studies in Latin America on the adoption of e-government that proposes a model adapted from technology acceptance theories, and therefore, it is of an exploratory nature. This research is a contribution to public officials and politicians in helping understand the needs of citizens regarding the use of government internet platforms.